Biomimetic siRNA-METTL3 loading nanosystem alleviates myocardial hypertrophy by regulating the FASN and SCD1 m6A modification - Peng Teng; Xiaoyi Dai; Yuefeng Wu; Yingying Wang; Zhen Jia; Chenqiu Wang; Shixing Wang; Runhua Li; Qi Zheng; Yiming Ni; Wei Jiang; Liguo Jian; et al. (Materials & Design, 2025)
RNA m6A modification plays a vital role in regulating cardiac function; however, its comprehensive mechanisms require further exploration. We observed that the expression of METTL3, a m6A methyltransferase, is significantly increased in hypertrophic hearts as well as during phenylephrine (PE)-induced cardiomyocyte hypertrophy in neonatal rat ventricular myocytes and transverse aortic constriction (TAC)-induced cardiac hypertrophy in mice. Concordantly, METTL3 knockdown could significantly inhibit PE-induced cardiomyocyte hypertrophy. RNA m6A-RIP-Seq analysis revealed that METTL3 may regulate lipid metabolism in cardiomyocytes by methylating the mRNA of fatty acid synthase (FASN) and stearoyl-CoA desaturase 1 (SCD1), thereby enhancing their stability. We developed a platelet liposome fusion membrane carrier that is loaded with siMETTL3. This carrier significantly reduces the expression of FASN and SCD1, enhances fatty acid oxidation, and promotes ATP production in cardiomyocytes. Overexpression of FASN and SCD1 can partially alleviate the impact on the aforementioned fatty acid oxidation-related effects caused by siMETTL3 platelet liposome fusion membrane carrier. Consequently, our siMETTL3 carrier alleviates TAC-induced pathological hypertrophy and improves cardiac function in vivo. These findings advance our understanding of METTL3-mediated RNA m6A modification in cardiac hypertrophy, holding promise for future treatments through our gene delivery carrier related to pathological cardiac hypertrophy.